A strontium (87Sr/86Sr) isoscape of Southern Ethiopia: implications for hominin land use and faunal mobility patterns - Asrat, Seminew; Lucchini, Francesco; Tafuri, Mary Anne; Aureli, Caterina; Gallinaro, Marina; Zerboni, Andrea; Fusco, Marianna; Spinapolice, Enza E. (Frontiers in Environmental Archaeology, 2025)
Tracing human and animal mobility behavior, land use, and exploitation strategies through strontium (Sr) isotope analysis is critical for archaeological and palaeoecological research. The development of an 87Sr/86Sr bioavailable baseline map, often termed isoscape, is a prerequisite for interpreting the Sr isotope composition of animal and human remains from an archaeological context. Despite the wealth of archaeological records dispersed across southern Ethiopia, we know little about bioavilable 87Sr/86Sr, which calls for a Sr isoscape to address key archaeological questions. Here, we present the first 87Sr/86Sr isoscape of southern Ethiopia produced using a geostatistical Ordinary Kriging approach through the analysis of water, plants, and soil leachate, combined with previously published datasets. We used the Middle Stone Age (MSA) site of Gotera as a case study and conducted 87Sr/86Sr isotope analysis of faunal tooth enamel. The results show that our novel baseline isoscape displayed heterogeneous 87Sr/86Sr isotope ratios in both the measured and predicted values (ranging from 0.703 to 0.712), consistent with geological units, with an accurate model performance evaluated through Leave-One-Out Cross-Validation (LOOCV) technique. The faunal tooth enamel analysis reveals that the Gotera fauna are of predominantly local origin, suggesting limited mobility and reliance on the exploitation of local resources across the Gotera area. This study on bioavailable isoscape and faunal 87Sr/86Sr isotopes highlights the potential of Sr isotope analysis to reconstruct past mobility patterns, spatial ecologies, and resource utilization strategies in Ethiopia.